Organizational Commitment: Leadership Agility, Career Path, Organizational Cultural - Junianti, Emmy (International Journal of Psychology and Health Science, 2023)
The purpose of the study is to determine whether there is an influence between leadership agility and organizational commitment, the influence of career path with organizational commitment, and organizational culture with organizational commitment, the research method used is qualitative with literature review by looking for scientific articles from several reputable and national international journals, research results from In this scientific article, first, there is an influence between the variables of Leadership Agility and Organizational Commitment from several review literature obtained, second, the influence of career path with organizational commitment with the results has an influence and is significant even though there are research results from (Giri et al., 2011) stating that organizational culture has an insignificant effect on organizational commitment, but the results of other studies from other scientific articles state a positive and significant influence, the third influence of organizational culture with organizational commitment from several scientific articles obtained there is a positive and significant influence. The results of this study represent the answer from researchers who are far from perfect and still need to be continued to further research with quantitative methods.